1992
DOI: 10.1002/iroh.19920770105
|View full text |Cite
|
Sign up to set email alerts
|

The Nitrogen Budget of a Shallow Lake (Großer Müggelsee, Berlin)

Abstract: The nitrogen budget of Lake Gr. Müggelsee (mean depth 4.85 m, area 7.12 km2) was calculated from weekly measurements of nitrogen transformations from 1978 to 1984. Common mass balances for nitrogen were completed by determination of dinitrogen fixation in order to calculate denitrification as residual budget component and resolved for distinct seasonal periods. N sedimentation was calculated from internal P balance. Influence of flushing rate on loss processes were analysed by comparison of years with very dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…In concert with this view, non-heterocyst cyanobacteria or green algae rather than heterocystous cyanobacteria are dominant in late summer in shallow hypertrophic Danish lakes, even when the concentration of nitrate is low (Jensen et al 1994). Moreover, it has been demonstrated by Levine & Schindler (1992) that N fixation is substantially less important in mesocosms with sediment than in those lacking sediment, and Dude1 & Kohl (1992) have shown that N fixation makes only a minor contribution (0.004-4%) to the nitrogen input in shallow German lakes.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In concert with this view, non-heterocyst cyanobacteria or green algae rather than heterocystous cyanobacteria are dominant in late summer in shallow hypertrophic Danish lakes, even when the concentration of nitrate is low (Jensen et al 1994). Moreover, it has been demonstrated by Levine & Schindler (1992) that N fixation is substantially less important in mesocosms with sediment than in those lacking sediment, and Dude1 & Kohl (1992) have shown that N fixation makes only a minor contribution (0.004-4%) to the nitrogen input in shallow German lakes.…”
Section: Resultsmentioning
confidence: 84%
“…relatively high N loading (Andersen 1974, Rip1 & Feibicke 1992), but they were high compared to rates obtained by less extensively N loaded lakes (Kelly et al 1987;Seitzinger 1988;Molot & Dillon 1993). The nitrogen retained in lakes is lost either by permanent burial in the sediment or by denitrification; other processes are of minor significance (Dude1 and Kohl 1992). Using phosphorus as a conservative tracer, Jensen et al (1991) estimated annual mean nitrogen burial in 69 mainly shallow Danish lakes to be 16 mg N mm2 d-l, or 23% of the total N loss.…”
Section: Resultsmentioning
confidence: 87%
“…In accordance with studies dealing with NO 3 -N budgets in lakes (e.g., Dudel and Kohl 1992;Windolf et al 1996), we consider the relative NO 3 -N loss rate k (Eq. 1) to be a function of lake internal processes such as denitrification, biological uptake, and net sedimentation as well as external loading.…”
Section: Resultsmentioning
confidence: 99%
“…In the Müggelsee, sediment dredging has indicated the precipitation of calcite due to high photosynthetic activity (Kozerski and Kleeberg ). This is commonly observed in productive hard‐water lakes such as the Müggelsee, where calcium is the main cation (Dudel and Kohl ; Driescher et al ), when photosynthetic uptake of CO 2 increases the pH, leading to oversaturation of calcite (Lampert and Sommer ; Heine et al ). The clear water phase was characterized by the collapse of most synchronicities, most strikingly the coherence between Chl a and water temperature and between Chl a and phycocyanin, and was accompanied by substantial decreases in Chl a , phycocyanin, O 2 and pH.…”
Section: Discussionmentioning
confidence: 94%